Zeitschrift für Physikalische Chemie : International journal of research in physical chemistry and chemical physics (Oldenbourg Wissenschaftsverlag, 1887)
Founded in 1887, the Zeitschrift für Physikalische Chemie covers the main developments in physical chemistry, placing with an emphasis on experimental research. It represents a combination ofdiscusses reaction kinetics and spectroscopy, surface research and electrochemistry, thermodynamics and the structure analysis of matter in its various conditions, among other topics.